Analysis of the role of education and sport in the heavy burden of obesity - Martyna Kłosińska; Iga Domańska; Aleksandra Gałuszka; Sandra Drabik; Natalia Sulkowska; Agnieszka Kaczyńska; Paulina Chmiel; Natalia Osial (Kazimierz Wielki University, 2023)
Obesity has become the global pandemic of the world. The epidemiological rise has only happened in recent decades. Unfortunately, the disease affects people of all ages. The most prominent characteristics of the disorder are excessive fat accumulation, body mass index exceeding the number of 30, and general lowering of the quality of life. The consequences are observed in the whole organism. The disruptions affect one's overall homeostasis. Certain diseases are specifically associated with excessive fat mass. When not properly managed, obesity leads to chronic illnesses and severe comorbidities, the most morbid one being death. Thus, effective therapeutic approaches are needed. Focus on education and physical activity are the best way to tackle this problem. The aim of this study is to check the factors and changes necessary to lose weight in obese patients in Poland. The main question regarded the role of sport and proper education in maintaining or losing weight in the Polish society. In order to analyse the issue, an Internet survey was prepared and disseminated in March and April 2023. Over half of the respondents have ever used a diet. Over 8 out of ten of them achieved the success in the set task. When asked about physical activity, the most respondents chose option 30-60 minutes per day. The preferred type of physical activity was most commonly walking. When asked if sport enabled the respondents to lose or maintain weight - 63,5% confirmed. 72% of respondents experienced education regarding healthy lifestyle, most commonly at home. Over 60% of respondents believed they were well informed about recommended behaviours. Over 50% of them confirmed their education is sufficient to lose weight. Maintaining healthy regimes is key to a healthy life. However, not all people are properly educated how to do that. In fact, there is a tendency of overestimation of one's education in those topics. All in all, proper experience and routines are necessary.